(untitled) (Journal of Computational Intelligence and Robotics, 2023)
Advancements in Natural Language Processing (NLP) have significantly enhanced the capabilities of automotive virtual assistants, revolutionizing user experience and safety in vehicles. This research article explores the integration of NLP technologies in automotive virtual assistants, focusing on improving user interaction and safety features. It covers topics such as voice-activated control systems, sentiment analysis for personalized responses, and NLP-driven predictive maintenance alerts for vehicles. The paper provides insights into the latest developments in NLP for automotive applications and discusses the potential benefits and challenges of integrating these technologies into vehicles.